Female Masculinities in Kevin Kwan’s Crazy Rich Asians: Power, Courage, Leadership, and The Reconfiguration of Gender Identity - Nur Latifah; Zulfan Sahri; Nurbaiti Ali; M. Safii (JOURNAL OF LANGUAGE, 2026)
This research analyses the portrayal of masculine qualities in female characters in Kevin Kwan's novel Crazy Rich Asians. Masculinity and femininity are socially constructed gender identities often associated exclusively with men and women respectively. However, scholars argue that masculinity does not belong solely to men and can be produced by women as well. While previous studies have examined gender representation in literature, limited attention has been given to how contemporary Asian popular fiction portrays female masculinity within the cultural tension between traditional Asian values and modern individualism. This study addresses that gap. Using Peter Lehman's masculinity theory as an analytical framework—identifying power, leadership, courage, and heroism—this research examines four female characters. The findings demonstrate that all four masculine qualities are present. Power is portrayed through Rachel Chu's ability to influence others and Eleanor Young's social dominance. Leadership is demonstrated by Eleanor Young's confident command. Courage is exhibited by Kerry Chu's defiance of societal expectations and Astrid Leong's bravery in confronting infidelity. Heroism is shown through Astrid Leong's concern for others and a maid who risked her livelihood to expose a harmful plot. This research demonstrates that masculine qualities are not biologically determined but socially constructed, challenging rigid gender stereotypes and redefining female identity as capable of integrating both feminine and masculine traits.